Penggunaan Bahasa Gaul pada Media Sosial TikTok: Penelitian - Michaelin Esteria Br Simanjuntak; Oktavia Manurung; Esa Wulan Br Pasaribu; Rolastri Simaremare; Muhammad Sany Islami Fasha (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The rapid growth of digital technology has led to the emergence of various social media platforms, one of which is TikTok, a space for young generations to express themselves. One prominent phenomenon is the widespread use of slang in both videos and comment sections. This article aims to describe the forms of slang that appear on TikTok and explain their functions in user communication. This study employs a descriptive qualitative method with data collected from screenshots of conversations and TikTok video content. The findings reveal that slang on TikTok appears in the form of acronyms, abbreviations, borrowed words from foreign languages, and contractions. Slang is primarily used as a medium of identity expression, social bonding, and adaptation to current trends. However, excessive use of slang may also cause misunderstandings among users who are not familiar with such expressions.